2015
DOI: 10.3389/fpls.2015.00659
|View full text |Cite
|
Sign up to set email alerts
|

Controlling weeds with fungi, bacteria and viruses: a review

Abstract: Weeds are a nuisance in a variety of land uses. The increasing prevalence of both herbicide resistant weeds and bans on cosmetic pesticide use has created a strong impetus to develop novel strategies for controlling weeds. The application of bacteria, fungi and viruses to achieving this goal has received increasingly great attention over the last three decades. Proposed benefits to this strategy include reduced environmental impact, increased target specificity, reduced development costs compared to convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(145 citation statements)
references
References 121 publications
2
136
0
2
Order By: Relevance
“…However, bioherbicides (fungi, bacteria and virus) seem to be a worthwhile subject for research because of their reduced environmental impact compared with chemical herbicides, despite several obstacles (selection of candidates, efficiency in the field, commercial profitability). Bioherbicides could be an alternative option for the management of weeds in the future …”
Section: Discussionmentioning
confidence: 99%
“…However, bioherbicides (fungi, bacteria and virus) seem to be a worthwhile subject for research because of their reduced environmental impact compared with chemical herbicides, despite several obstacles (selection of candidates, efficiency in the field, commercial profitability). Bioherbicides could be an alternative option for the management of weeds in the future …”
Section: Discussionmentioning
confidence: 99%
“…The development of safe and eco-friendly herbicides is an emergent necessity to control weeds in these cultivations (Yang et al 2014). Biological weed control strategies can potentially address this need and provide novel modes of action that will inhibit the growth of weeds that are resistant to more commonly used herbicides (Harding and Raizada 2015). Inundative biological control (which refers to the application of propagation of fungal spores or bacterial suspensions in concentrations that would not normally occur in nature with the intention of destroying a pest species within a managed area) is the strategy more employed (Bailey et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the future trend is the production of herbicidal compounds by fermentation, extract it from fermented broth, and use this compound in a more stable formulation. This strategy will not be limited on the continued survival of a given organism in an uncontrolled environment (Harding and Raizada 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Recent discoveries have indicated that herbicides might be generated from microbial sources such as plant endophytes to protect plants from invasive and parasitic plant species (1, 2). Some of these endophytes produce antiherbicide properties that can counteract the function of commercial herbicides.…”
Section: Genome Announcementmentioning
confidence: 99%